Value of sub18F-FDG-PET in clinical management of patients with osteosarcoma - Bohuslavizki, Karl H. (Radiology and oncology (Ljubljana), 2000)
The aim of this study was to define the value of 18F-FDG PET in clinical management of patients with osteosarcoma based on current treatment regimen. Patients and methods. A total of 18 patients (4 female, 14 male) aged from 14 to 63 years with primary osteosarcoma (n=6) or suspect for relapse of osteosarcoma (n=12) were investigated retrospectivety. First, all patients underwent conventional diagnostic work-up, i.e. X-ray and MRI of the primary bone lesion, CT scan of the chest as well as conventional bone scan. In addition, whole-body PET-images were acquired on an ECAT EXACT 47 (921) with an axial field-of-view of 16.2 cm (Siemens, CTI) after intravenous injection of 370 MBq18F FDG. All tumor-suspicious PET findings were evaluated histologically. Results of histology, PET findings and conventional imaging were correlated on a lesion-by-lesion basis. Results. 18F-FDG-PET clearly depicted all primary osteosarcomas in 6 patients and a relapse of osteosarcomain two patients. In the remaining 10 patients histology could not confirm a relapse of osteosarcoma. Eight out of 18 patients showed further lesions with an abnormal 18F-FDG-uptake. These lesions were predominantly located in the lung (n=5), in the skeleton (n=3), and in the inguinal region (n=1). Three of 8 patients had primary diagnosis of osteosarcoma and 5 were suspected to have tumor relapse. All lesions but the lesion of the inguinal region turned out to be metastases of osteosarcoma. However, therapeutic management must be taken into consideration when interpreting these encouraging results. Since the vast majority of patients are known to have micro metastases at the time of diagnosis, combined treatment consisting of neoadjuvant chemotherapy and surgical resection of the tumor is the standard treatment. Thus, 18F FDG-PET has no significant impact in primary diagnosis ofosteosarcoma. (Abstract truncated at 2000 characters.)
Keywords: Biopsy; Deoxyglucose; Diagnosis; diagnostika; Fluorine; Neoplasm staging; Osteosarcoma; osteosarkom; Pathology; radiologija; rak (medicina); sarkom; Tomography, emission-computed; Treatment outcome; zdravljenje